TANAMAN BERPERAWAKAN SEDANG DAN TINGGI DI PEKARANGAN TELUKNAGA, CITEUREUP DAN PACET - ATMOWIDJOJO, S.; FACHRUROZI, Z. (Research Center for Biology-Indonesian Institute of Sciences, 1985)
S. ATMOWIDJOJO & Z. FACHRUROZI. 1985. Plants with medium and tall statures in the kitchen gardens in Teluknaga, Citeureup and Pacet. Berita Biologi 3(2): 37 - 48. Analyses on plants of kitchen gardens showed the presence of 25 species of middle-stratum and 23 species of higher stratum in three studied localities. For the middle-stratum, only 28% were found in common, while the higher stratum 21.73%. Bananas were the most common middle-stratum found in 3 localities, coconut and mango tiees were the most common in Teluknaga, and rarnbutans in Citeureup. Fertilizers were used only at the most 25%, but for clove and citrus trees in Citeureup and Pacet by more than 50% growers. Most of the fertilizer used was manure, but for higher stratum plants in Teluknaga synthetic fertilizers were used more. Pest management was not commonly practiced. If done, synthetic insecticides were generally used.